Beauty, Underage Drinking, and Adolescent Risky Behaviours - Colin P. Green; Luke B. Wilson; Anwen Zhang (Institute of Labor Economics (IZA), 2022)
Physically attractive individuals experience a range of advantages in adulthood including higher earnings; yet, how attractiveness influences earlier consequential decisions is not well understood. This paper estimates the effect of attractiveness on engagement in risky behaviours in adolescence. We find marked effects across a range of risky behaviours with notable contrasts. More attractive adolescents are more likely to engage in underage drink- ing; while they are less likely to smoke, use drugs, or practice unprotected sex. Investigation into the underlying channels reveals that popularity, self-esteem, and personality attractiveness have roles as mechanisms. Our findings suggest physical attractiveness in adolescence carries long-lasting consequences over the life course.
Keywords: I12; J10; 330; beauty; risky behaviours; adolescent development